2017
DOI: 10.1093/pcp/pcx198
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Function of the Populus SABATH Family Reveal That a Single Amino Acid Change Results in a Substrate Switch

Abstract: Evolutionary mechanisms of substrate specificities of enzyme families remain poorly understood. Plant SABATH methyltransferases catalyze methylation of the carboxyl group of various low molecular weight metabolites. Investigation of the functional diversification of the SABATH family in plants could shed light on the evolution of substrate specificities in this enzyme family. Previous studies identified 28 SABATH genes from the Populus trichocarpa genome. In this study, we re-annotated the Populus SABATH gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 36 publications
2
30
0
Order By: Relevance
“…The alignment of the Betula SAMT (Fig 2) and previously functionally characterized members of SABATH family suggests that Betula SAMT probably methylates both SA and the structurally similar substrate BA [54]. It has also been experimentally proven that members of the SABATH methyltransferase family catalyze multiple substrates with different K m values [8,50,54,55]. Additionally, it has been suggested that a single amino acid substitution might play a critical role in the specificity of SAMT/BSMT with SA and BA [72].…”
Section: Comprehensive Bioinformatics Analysismentioning
confidence: 86%
See 4 more Smart Citations
“…The alignment of the Betula SAMT (Fig 2) and previously functionally characterized members of SABATH family suggests that Betula SAMT probably methylates both SA and the structurally similar substrate BA [54]. It has also been experimentally proven that members of the SABATH methyltransferase family catalyze multiple substrates with different K m values [8,50,54,55]. Additionally, it has been suggested that a single amino acid substitution might play a critical role in the specificity of SAMT/BSMT with SA and BA [72].…”
Section: Comprehensive Bioinformatics Analysismentioning
confidence: 86%
“…vinifera , and A . thaliana [ 4 , 50 , 52 , 54 ]. However, very little is known about the genetic architecture of SAMT and SABP2 in the ecologically important tree species of the genus Betula .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations